1999
DOI: 10.1096/fasebj.13.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and free radicals impair the antioxidant properties of serum albumin

Abstract: Epidemiological data consistently show that reduced levels of serum albumin, which is the most abundant protein in plasma, are associated with an increased mortality risk. Various biological properties evidenced by direct effects of the albumin molecule may explain its beneficial effects. The present work aimed to investigate in vitro whether glycation or free radicals or both factors would affect the antioxidant properties of bovine serum albumin (BSA). Glycation was performed by long-term incubations (60 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
171
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 274 publications
(181 citation statements)
references
References 57 publications
8
171
1
1
Order By: Relevance
“…Both in the red blood cell hemolysis and in ORAC assays, the presence of copper in BSA samples seems to reinforce the free radical trapping capacities of albumin. However, the strengthening in the antiradical capacity of glycated albumin following copper induced-oxidation appears to be in total opposition with previous findings [56]. Even if antioxidant property of albumin seems not to be impaired, there is evidence that the protective role of the protein on cellular system is dramatically altered in the presence of metals, as attested by MTT and FACS results.…”
Section: Discussioncontrasting
confidence: 61%
“…Both in the red blood cell hemolysis and in ORAC assays, the presence of copper in BSA samples seems to reinforce the free radical trapping capacities of albumin. However, the strengthening in the antiradical capacity of glycated albumin following copper induced-oxidation appears to be in total opposition with previous findings [56]. Even if antioxidant property of albumin seems not to be impaired, there is evidence that the protective role of the protein on cellular system is dramatically altered in the presence of metals, as attested by MTT and FACS results.…”
Section: Discussioncontrasting
confidence: 61%
“…21,23 Thus, albumin may represent a quantitatively important component in the efficient antiox- Figure 4, aliquots of total RNA (20 g) isolated from HepG2 cells were electrophoresed, and Northern blot analysis was performed with the use of corresponding cDNA probes specific for HSA or GAPDH as described in Methods. B, Quantitative analysis was performed by scanning of blots and normalized against GAPDH.…”
Section: Discussionmentioning
confidence: 99%
“…22 Moreover, our recent data bring further support to the proposal that in addition to its plasma concentration, the quality of the albumin molecule may be related to its biological properties. 23 We reported that glucose and free radicals impair the antioxidant properties of serum albumin. The serum level of albumin is mainly related to its synthesis and catabolism but also to its transcapillary escape.…”
mentioning
confidence: 97%
“…Researches performed in our group focus on the effects of oxidative modifications induced by the glycation of albumin on its structure, antioxidant properties, and on cell physiology [6][7][8][21][22][23][24][25][26][27]. The implication of glycoxidized albumin in the generation of oxidative stress and damages on cells still needs to be better specified.…”
Section: We Took Advantage Of This Laboratory Training To Describe Rementioning
confidence: 99%